Regionalism without regions : reconceptualizing Ukraine's heterogeneity - Schmid, Ulrich 1965- HerausgeberIn; Myshlovska, Oksana HerausgeberIn (Leipzig studies on the history and culture of East-Central Europe, 2019)
"This collective volume shows how Ukraine can best be understood through its regions and how the regions must be considered against the background of the nation. The overarching objective of the book is to challenge the dominance of the nation-state paradigm in the analyses of Ukraine by illustrating the interrelationship between national and regional dynamics of change. The authors--historians, sociologists, anthropologists, economists, literary critics and linguists from Ukraine, Poland, Switzerland, Germany and the USA--explicitly go beyond the perspective of an entity defined by traditional political borders and cultural, economic, historical or religious stereotypes. The research project that led to the composition of the book combined quantitative (statistical surveys conducted across Ukraine) and qualitative (in-depth interviews and focus-group discussion) methods. The authors came to the conclusion that regionalism as a defining phenomenon of Ukraine is more prominent than the regions themselves. This approach regards Ukraine as a construct in flux where different discourses intersect, concur and eventually merge through the lenses of various disciplines and methodologies"--